Plate-rod associated to the toggle pin method in dog femur - Krusch Bello, Lucas; Curvello de Mendonça Müller, Daniel; José Chávez Silva, Álvaro (Pubvet, 2020)
The current work aims to report the use of rod-plate system associated with toggle pin method for correction of comminuted femoral diaphyseal fracture with craniodorsal coxofemoral dislocation on the same limb in a dog. The dislocation was corrected through installation of the toggle pin method, in which the femur's round ligament is replaced with a thick resistant thread, capable to pattern the round ligament's functions. The osteosynthesis was operated with a blocked bone plate, size 3.5 mm and an intramedullary pin of 2.5 mm, a system known as rod plate, used to treat large fracture gaps. The denoted system offers good stability and support for biological osteosynthesis. The animal was evaluated on its 10th postoperative day along with the removal of the stitches. The patient was walking normally and, according to the tutors, already leaning on the limb on the first day after surgery. It can be stated that the coupling of these methods ensured an adequate early return of limb function in the postoperative period. When necessary, the two techniques can be used together, since the principles and indications of each are respected.
Keywords: fracture; dislocation; osteosynthesis; intramedullary pin; bone plate